Early Alterations of Lymphocyte Subsets in Acute Respiratory Distress Syndrome Caused by Acinetobacter baumannii Pneumonia: A Prospective Observational Study - Cheng, Wei; Zhang, Jiahui; Li, Dongkai; Bai, Guangxu; Han, Wen; Chen, Jianwei; Wang, Hao; Cui, Na (Frontiers in Medicine, 2021)
Background: To prospectively observe the early alterations of lymphocyte subsets in ARDS caused by Acinetobacter baumannii. Methods: ARDS patients admitted to our ICU between January 1, 2017 and May 30, 2020 were selected. We enrolled all the pulmonary ARDS caused by Acinetobacter baumannii pneumonia who required mechanical ventilation or vasopressors. All the available clinical data, follow up information and lymphocyte subsets were recorded. Results: 87 of all the 576 ARDS patients were enrolled. The 28-day mortality of the enrolled patients was 20.7% (18/87). The T lymphocyte count (452 vs 729 cells/ul, P = 0.004), especially the CD8+ T lymphocyte count (104 vs 253 cells/ul, P = 0.002) was significantly lower in non-survivors, as were counts of the activated T cell subsets (CD8+CD28+ and CD8+CD38+). The CD8+ T cell count was an independent risk factor for 28-day mortality, and a cutoff value of 123 cells/ul was a good indicator to predict the prognosis of ARDS caused by Acinetobacter baumannii pneumonia, with sensitivity of 74.6% and specificity of 83.3% (AUC 0.812, P < 0.0001). Conclusions: Lower CD8+ T cell count was associated with higher severity and early mortality in ARDS patients caused by Acinetobacter baumannii pneumonia, which could be valuable for outcome prediction.